Hierarchical Zeolites and their Catalytic Performance in Selective Oxidative Processes. Issue 8 (27th March 2015) - Ojeda, Manuel; Grau‐Atienza, Aida; Campos, Rafael; Romero, Antonio A.; Serrano, Elena; Maria Marinas, Jose; García Martínez, Javier; Luque, Rafael
Abstract: Hierarchical ZSM‐5 zeolites prepared using a simple alkali treatment and subsequent HCl washing are found to exhibit unprecedented catalytic activities in selective oxidation of benzyl alcohol under microwave irradiation. The metal‐free zeolites promote the microwave‐assisted oxidation of benzyl alcohol with hydrogen peroxide in yields ranging from 45–35 % after 5 min of reaction under mild reaction conditions as well as the epoxidation of cyclohexene to valuable products (40–60 % conversion). The hierarchically porous systems also exhibited an interesting catalytic activity in the dehydration of N, N ‐dimethylformamide (25–30 % conversion), representing the first example of transition‐metal free catalysts in this reaction. Abstract : Ambitious not siliceous: Desilicated hierarchical zeolites hold promise as catalytic systems. The feasibility of using these hierarchical zeolites, with and without iron oxide nanoparticles, in selective oxidation processes is investigated, taking advantage of terminal AlOH groups to generate redox sites in zeolites. The test reactions, under microwave irradiation, are the oxidation of benzyl alcohol to benzaldehyde, the epoxidation of cyclohexene, and the multistep conversion of N, N ‐dimethyl formamide (DMF).